Switching channels : organization and change in TV broadcasting - Caves, Richard E. (Harvard University Press, 2005)
Media critics invariably disparage the quality of programming produced by the U.S. television industry. But why the industry produces what it does is a question largely unasked. It is this question, at the crux of American popular culture, that Switching Channels explores.